PENGARUH DISTRAKSI VIRTUAL REALITY TERHADAP PERUBAHAN DENYUT NADI SELAMA PROSEDUR ANESTESI LOKAL JET INJEKTOR PADA PERAWATAN GIGI ANAK - Septriyani Kaswindiarti; Ferdian Ilham Khoirudin; Busyro Hanun Nisa; Wahyuning Asri Pari Purnomo Sari (Universitas Baiturrahmah, 2021)
Introduction: Pain conditions can cause physiological responses in the form of increased pulse rate. A local anesthetic procedure with a syringe is given to minimize pain during an invasive procedure in children's dental treatment, but the procedure can also cause pain. A jet injector is a new innovative anesthetic tool that can anesthetize certain areas without using a needle with minimal pain, but the shape and size of the jet injector, as well as the shocking sound of the device, can affect the pain perception of children, therefore a distraction method is needed to divert attention children from pain stimulus, one of them by using virtual reality. This research purposed to determine the effect of virtual reality distraction on changes in pulse during local anesthetic procedures with jet injectors in pediatric dental care. Methods: The research method used in this study is a quasiexperimental with Pretest-Posttest non-Equivalent Control Group Design. This design is used to find out the comparison between the treatment group and the non-treatment group. Changes in pulse rate before and during the anesthesia procedure in both groups were analyzed using the Independent T-Test analysis. Results: Based on the results of the Independent T-Test, it was found that the T-test Sig. (2- tailed) is 0.001 (p <0.05) so the data obtained is significant. Conclusion: Virtual reality distraction influences changes in pulse rate smaller than without distraction during local anesthetic procedures with jet injectors in pediatric dental care.